Rate and Amplification of Drug Resistance among Previously-Treated Patients with Tuberculosis in Kampala, Uganda - Temple, Beth (2008)
BACKGROUND: Drug-resistant Mycobacterium tuberculosis has emerged as a global threat. In resource-constrained settings, patients with a history of tuberculosis (TB) treatment may have drug-resistant disease and may experience poor outcomes. There is a need to measure the extent of and risk factors for drug resistance in such patients. METHODS: From July 2003 through November 2006, we enrolled 410 previously treated patients with TB in Kampala, Uganda. We measured the prevalence of resistance to first- and second-line drugs and analyzed risk factors associated with baseline and acquired drug resistance. RESULTS: The prevalence of multidrug-resistant TB was 12.7% (95% confidence interval [95% CI], 9.6%–16.3%). Resistance to second-line drugs was low. Factors associated with multidrug-resistant TB at enrollment included a history of treatment failure (odds ratio, 23.6; 95% CI, 7.7–72.4), multiple previous TB episodes (odds ratio, 15.6; 95% CI, 5.0–49.1), and cavities present on chest radiograph (odds ratio, 5.9; 95% CI, 1.2–29.5). Among a cohort of 250 patients, 5.2% (95% CI, 2.8%–8.7%) were infected with M. tuberculosis that developed additional drug resistance. Amplification of drug resistance was associated with existing drug resistance at baseline (P<.01) and delayed sputum culture conversion (P<.01). CONCLUSIONS: The burden of drug resistance in previously treated patients with TB in Uganda is sizeable, and the risk of generating additional drug resistance is significant. There is an urgent need to improve the treatment for such patients in low-income countries.